The Effect of Green Campus Branding and Employability on Private University Choice - Desta Sulaesih Mursyidah; Yanti Setiowati; Nining Latianingsih; Dewi Yolanda Putri; Iis Mariam; Raden Minda Kusumah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the effects of Green Campus Branding and Perceived Green Employability on students’ decisions to choose private universities, with Brand Trust as a mediating variable. Methodology: The study was conducted in Bandung using a quantitative, causal explanatory design. Data were collected through an online questionnaire from 200 prospective and first-year students. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) in SmartPLS. Results: Green Campus Branding does not have a significant direct effect on university choice decisions (? = 0.110; p > 0.05), but becomes significant through full mediation by Brand Trust (? = 0.230; p < 0.001). Perceived Green Employability has a significant direct effect (? = 0.210; p < 0.05). Brand Trust also shows a strong direct effect on university choice decisions (? = 0.540; p < 0.001). The model explains 61.5% of the variance in university choice decisions (R² = 0.615). Conclusions: Green marketing strategies are effective only when supported by strong Brand Trust. Limitations: This study is limited to one geographic area and uses self-reported data. Contributions: This study enriches green marketing and higher education research and provides practical insights for university marketing strategies.